SERVIÇO DE CONVIVÊNCIA PARA CRIANÇAS E ADOLESCENTES: UM EXEMPLO DE TRAVESSIA PARADIGMÁTICO - Carnevalli, Henrique Abarca Schelini (2023)
The House of the Small Citizen is now a Service ofCoexistence and Strengthening of Links for Children and Adolescents.After the National Classification of Social Assistance Services, in2009, which was since its inception in 1998, a Social Project of theMunicipality of Marília / SP, followed the Technical Guidelines of theFederal Government and to be referenced by the Reference Center forAssistance Social, in which he was responsible for putting intopractice the Basic Social Protection and the Integral FamilyAssistance Program. After years of the promulgation of the ECA, thecreation of the Single System of Social Assistance and theStandardization of these Services, this project becomes a transitionmodel to be analyzed by two points. Firstly, regarding theparadigmatic changes that occurred between the Irregular SituationDoctrine, proper to the Minors Code, and the Integral ProtectionDoctrine described by the ECA. Secondly, with regard to the newconceptions of care coming from the passage "Social Project" -"Service Typified '' in which to live and create bonds became a methodof professional action. Thus, based on these counterpoints andthrough the profile of the Coordinators, Social Assistants andEducators of the Services, their conceptions of children, adolescentsand their families, and of the relational practice between CRAS andCoexistence Service, we find that we are living a decisive moment forSocial Assistance in Brazil: either a more expressive investment ininfrastructure, hiring of personnel and professional training or we willsee the socio-welfare services become innocuous in the face of theincreasing challenges of the Brazilian reality.